2010
DOI: 10.1007/s11356-010-0398-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of tetracycline exposure on growth, antioxidative and genetic indices of wheat (Triticum aestivum L.)

Abstract: Tetracycline may have potential physiological, biochemical, and genetic toxicity to plant cells, and chromosome aberration and MDA might be sensitive bioindicators for tetracycline contamination than the other plant characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 41 publications
1
45
2
Order By: Relevance
“…In this study, the MDA contents were significantly higher in high erythromycin concentration treatments compared to the control, indicating that high erythromycin concentrations induced stronger peroxidation and caused more serious damage to the cell membrane. However, a slight increase in the MDA content was observed at low concentrations (<0.01 g L −1 ) of erythromycin, suggesting less oxidative stress on M. flos-aquae and possibly accounting for the lack of growth inhibition [43].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this study, the MDA contents were significantly higher in high erythromycin concentration treatments compared to the control, indicating that high erythromycin concentrations induced stronger peroxidation and caused more serious damage to the cell membrane. However, a slight increase in the MDA content was observed at low concentrations (<0.01 g L −1 ) of erythromycin, suggesting less oxidative stress on M. flos-aquae and possibly accounting for the lack of growth inhibition [43].…”
Section: Discussionmentioning
confidence: 92%
“…Liu et al [29] found that Florfenicol stimulated the growth of Skeletonema costatum at concentrations of 0.5, 1.0 and 2.0 mg L −1 and significantly inhibited growth at concentrations > 2.0 mg L −1 . Xie et al [43] showed that tetracycline at 0.5-10 mg L −1 stimulated seed germination, cell mitotic division, and growth of wheat seedlings; however, tetracycline at the high concentrations (10-300 mg L −1 ) significantly inhibited these parameters in a concentration-dependent manner. In our study, low concentrations of erythromycin promoted the growth of M. flos-aquae, possibly due to the promotion of certain enzymes involved in physiological and biochemical reactions at certain erythromycin concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes in morphological parameters are a secondary effect of toxic action of xenobiotics. Phytotoxic effects of tetracycline include reduction of the length of wheat roots and stems, and a decrease of their mitotic index (Xie et al, 2011), also lucerne responds identically when exposed to oxytetracycline (Kong et al, 2007). In order to counteract the reduction in water content plants accumulate protective compounds (Yin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline antibiotics are the most frequently found in agricultural soils throughout the world, and the residual compounds result in a potential threat to both plants and soil organisms even at concentrations that are commonly detected in agricultural soils (Aga et al 2005;Thiele-Bruhn and Beck 2005;Sarmah et al 2006;Karcı and Balcıoğlu 2009;Goetsch et al 2012). A mass of investigation on the occurrence of antibiotic resistance genes (ARGs) was derived from the selection by antibiotics in recent years, indicating the contamination of natural environments or their antagonistic effects to soil microorganisms and a latent environmental threat besides the promoted genetic toxicity to plants in the soil (Xie et al 2011;Gao et al 2013;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%